Urbanismo anfibio. Renovación urbanística, en búsqueda de la resiliencia en el territorio inundable de la Virginia Risaralda (2022)
This is an urban project, directed and focused on the river banks near municipal capitals that are affected by floods at different times of the year, areas where historically there has been inadequate treatment, ignoring its effects on the municipalities and the effects that It can be generated in the protection zones of this vital liquid.